Electrical muscle stimulation as an effective recovery modality - Hansen, D. M. (New Studies in Athletics, 2015)
Electrical muscle stimulation (EMS) has been used to enhance sport performance and rehabilitation from injury for over 50 years and there is a substantial body of scientific research to support the practice. In addition, some coaches and performance professionals have taken advantage of advances in available technology to use EMS to support recovery from training and competition. Research in this area is less complete but sport scientists are now taking a closer look at the concept. The author, an experienced strength and conditioning coach, shares his experience with the use of EMS in the following areas: 1) enhancing blood circulation and the delivery of oxygen and nutrients to muscles and other soft-tissues, 2) enhancing muscle activation to assist with preparation for training or competition, 3) increasing the muscle lengthening effect of Proprioceptive Neuromuscular Facilitation stretching, 4) managing muscle soreness and pain after training sessions. In each case he provides an overview of the use of EMS and the expected benefits. In his conclusion, he cautions that while EMS is an important practical tool for bolstering already established recovery methods, it should be used in combination with them and not as a substitute.